Frankenstein [large type] - Shelley, Mary Wollstonecraft, 1797-1851 (Kennebec Large Print perennial favorites collection., 2009)
A monster created by scientist Victor Frankenstein from parts of corpses and brought to life develops loathing for himself and hatred for his creator as he learns to think for himself.